Myriospora kunyuensis (Acarosporaceae, lichenized Ascomycota), a new species from the eastern coast of China - Wang, Jia-Xin; Liang, Fu-Hui; Zhou, Shu-Nuo; Hu, Ling (Phytotaxa, 2025)
The new species Myriospora kunyuensis is described from Kunyu Mountain Nature Reserve, Shandong Province, China, based on molecular, chemical and morphological data. It is characterized by the presence of stictic acid, thick epicortex (up to 40 μm thick) and small apothecia (up to 40 μm wide). Phylogenetic analyses support the placement of the new species in Myriospora. A worldwide key to all known Myriospora species, including 13 names, is provided.